The emerald horizon : the history of nature in Iowa - Mutel, Cornelia Fleischer (Bur oak book., 2008)
Since so much of the tallgrass state has been transformed into an agricultural landscape, Mutel focuses on understanding today's natural environment by understanding yesterday's changes. After summarizing the geological, archaeological, and ecological features that shaped Iowa's modern landscape, she recreates the once-wild native communities that existed prior to Euroamerican settlement. Next she examines the dramatic changes that overtook native plant and animal communities as Iowa's prairies, woodlands, and wetlands were transformed. Finally she presents realistic techniques for restoring n.